The problem of American Loans and Credits for Czechoslovakia in 1945–1948 - A. V. Zorin (Vestnik MGIMO-Universiteta)
The article is devoted to one of the aspects of the US European policy after World War II: the issue of loans and credits to affected countries. Using the example of Czechoslovakia, the author tries to answer a number of important questions: did Washington have a sound financial and economic policy towards this country, what goals did it pursue, what were its results? The study is based on the US Department of State archive documents and papers of the American ambassador to Czechoslovakia L.A. Steinhardt. The US financial policy towards Czechoslovakia in the early post-war years was the subject of intense debate in the United States. The author reveals evidence of serious disagreement between economic and political divisions of the State Department about providing of financial assistance to Prague, its size and terms of lending. Particular attention is paid to Steingardt’s position and his attempts to determine American loans and credits to Prague by upholding the property interests of American citizens. These disagreements hindered the development of a single thoughtful course regarding the Czechoslovak Republic and complicated diplomatic relations with Prague; negotiations on the allocation of large loans for the economic recovery of the Czechoslovak Republic dragged on. A fundamental role in the establishment of a new US political course had Secretary of State James Byrnes’ decision, made in the fall of 1946, on the inadmissibility of providing assistance to countries that have taken anti-American positions. This approach was finally entrenched after the Communists coup in Czechoslovakia in February 1948, when the country entered the Soviet sphere of influence. The article concludes that the post-war US policy was not distinguished by integrity and thoughtfulness.